Technical Evaluation of Remote Laboratories in an Engineering Educational Network. (2015) - German-Sallo, Zoltan; Grif, Horatiu-Stefan; Gligor, Adrian
Abstract: This work describes an Engineering Educational Network based on remote labs and proposes a methodology to perform a technical evaluation of this network. The educational network is located in the Maghrebian countries, Morocco, Tunisia and Algeria. The proposed technical evaluation strategy is build starting from international specific standards as ISO/IEC 25010:2011 and is focused on functional suitability and its three components, functional completeness, functional correctness and functional appropriateness. This work is carried out within the framework of the European Tempus IV project called "eSience" and sixteen partners from seven different countries are involved.